Adherence to the mediterranean diet and risk of hypoglycemia in insulin-treated type 2 diabetic patients - Caterina Formichi; Sonia Caprio; Stefano Auddino; Felicia Rizza; Barbara Paolini; Laura Nigi; Francesco Dotta (Human Nutrition & Metabolism, 2025)
Background and aims: Lifestyle intervention, aimed at weight loss and increasing physical activity, is widely known as the first-line treatment in diabetes. Adherence to a medical nutritional therapy (MNT) is even more relevant in patients on insulin therapy. However, data on the relationship between diet composition and glycemic control indexes derived from continuous glucose monitoring (CGM) in type 2 diabetes (T2D) are scarce and inconsistent. Our aim was to evaluate the association between adherence do Mediterranean diet (MD) and CGM metrics in a cohort of T2D patients treated with insulin. Methods and results: We retrospectively collected data of 25 patients with T2D on insulin therapy, at the Diabetes Unit of University Hospital in Siena. They were prescribed a flash glucose monitoring (FGM) system and accepted to answer the MEDLIFE questionnaire, a validated tool designed to explore the adherence to MD. Adherence to MD did not seem to influence glycemic control indexes in our cohort. It is worth mentioning that the risk of hypoglycemia and time spent in hypoglycemia was found to be highly influenced by alcohol consumption, even in minimal amounts (according to national guideline recommendations). Conclusion: Nutritional counselling for patients with insulin-treated T2DM should include a focus on alcohol consumption – ideally to be avoided - and related hypoglycemic risk.